Regional anesthesia for hip surgery: A review of current approaches and their application to clinical practice - Tiberio Evangelista; Camilla Pugno; Simone Finazzi; Alessandro Colombi; Dario Bugada (Saudi Journal of Anaesthesia)
Hip surgery is extremely common and ranges from surgery for hip fracture to elective procedures in younger adults. Pain can mark the postoperative period and compromise functional recovery. Nevertheless, major comorbidities may occur in the perioperative period, especially in elderly fragile patients. The approach to patients undergoing hip surgery has significantly evolved, focusing on multimodal strategies to optimize pain control while minimizing side effects, prompting patients’ recovery. The seek for motor-sparing, analgesic techniques with a better risk benefit profile has promoted the application of new peripheral nerve blocks, with special attention paid to the newest fascial plane blocks. However, significant interest is addressed toward other outcomes (such major comorbidities and deaths) that may influence intermediate and long-term recovery. Specific strategies have been investigated to improve outcomes after hip surgery in elderly patients, considering the higher risk for complications, including delirium. In this narrative review, we aim to summarize the role of regional anesthesia and analgesia in the context of hip surgery by detailing on the effects of regional anesthesia on major outcomes. Considering the specific innervation of hip joint, we summarize the available evidence on newer peripheral nerve blocks for hip patients by focusing on potential complications associated with each technique, especially the occurrence of motor block. In this review, we aim to provide an updated and concise overview of the available evidence to help the reader planning the most appropriate strategy for hip surgery.